Analisis Sikap Keluarga Dalam Penerapan Program Indonesia Sehat Dengan Pendekatan Keluarga (PIS-PK) - Ifon Driposwana Putra; Ulfa Hasana (STIKes Payung Negeri Pekanbaru, 2019)
The Ministry of Health has determined that the operational strategy for health development is through the Healthy Indonesia Program with a family approach (PIS-PK), with the aim of improving the health status and nutritional status of the community starting from a basic-based approach, namely the family. However, in its implementation, this program has not produced maximum results as evidenced by the still low level of health in the community, especially in the working area of ​​Pekanbaru City Sail Puskesmas with a percentage of 24.85% of households behaving clean and healthy (PHBS), even though health workers on an ongoing basis there is always training in carrying out this program. Therefore, the purpose of this study is that researchers are interested in knowing the attitudes of families in accepting the direction of health workers to implement PIS-PK. This type of research is analytic descriptive with 100 family respondents. The analysis of family attitudes in implementing PIS-PK shows that more than half the percentage of families is positive at 66%.